A-103 Predicting Time to Loss of Independent Living in Alzheimer's Clinical Syndrome. (17th August 2022) - Helphrey, Jessica H; Fatima, Hudaisa; Conley, Michael; Sawyer, Jennifer; Schaffert, Jeffrey; Palka, Jayme; Rossetti, Heidi; Carlew, Anne; Cullum, Munro; Lacritz, Laura; Hart, John; LoBue, Christian
Abstract: Objective: Estimating when full time care will be needed in Alzheimer's Clinical Syndrome (ACS) is difficult. This is due to limited research identifying the factors associated with loss of independent living (LOI), which may differ across dementia stages. Thus, we examined which clinical and neuropsychological factors predict LOI in the early-to-middle and late stages of ACS. Method: Using the National Alzheimer's Coordinating Center dataset, individuals with ACS aged ≥50 years with no prior stroke were studied. LOI was based on self/informant report of progressing from requiring some assistance with complex activities at ACS diagnosis to needing assistance with basic activities. Four survival analyses were conducted to predict LOI (M time to LOI = 3.6 visits), for the early-to-middle (MMSE at diagnosis ≥20; N = 3128) and late stages of ACS (MMSE≤19; N = 737). Fifteen clinical predictors at time of ACS diagnosis were examined, followed by neuropsychological test scores added to the models. Results: In early-to-middle ACS, a faster time to LOI was predicted by incontinence, apathy, delusions, and anxiety, along with poorer processing speed, memory, category fluency, and executive function scores (p < 0.05). In the late dementia stage, incontinence, delusions, and lower processing speed predicted faster time to LOI (p < 0.05). Conclusions: Factors gathered at the time of ACS diagnosis from a clinical interview and neuropsychological assessment are predictive of time to LOI, with few differences for the early-to-middle and late stages of ACS. Developing an algorithm to estimate time to LOI will be important for future research to aid in planning future care for individuals with ACS.